Needs Analysis Research in the Arab World (2000 – 2019): Contexts and Data Collection Instruments and Sources Triangulation - Mohammed, Abuelgasim Sabah Elsaid (Language Circle: Journal of Language and Literature, 2022)
This study aimed at reporting the contexts of interest in needs analysis research (NAR) in the Arab World (2000 – 2019) and describing the adoption of triangulation in data collection instruments and data sources. A purposive sample of 48 published NAR was subjected to content analysis. Results revealed that needs analysis studies (NASs) in the Arab World (2000 – 2019) are interested in EAP context more than other contexts such as English for Medical Purposes (EMP) and English for Occupational Purposes (EOP). In addition, most of the NASs adopted one data collection tool and consulted outsiders as sources of data. In addition, the study found that there is lack of method and/or source interaction. In general, NAR in the Arab World suffers from several shortcomings. Based on these results, the study recommended that NA researchers in the Arab World should pay more attention to other ESP contexts. In addition, they need to address issues related to triangulation to lend reliability to their data.